IMPLEMENTASI PERENCANAAN DAN PENGEMBANGAN KARIR UNTUK MENINGKATKAN KESIAPAN MAHASISWA MEMASUKI DUNIA KERJA - Kurniawan, Muhammad Rizki Dwi; Putri, Devina Fatikhah; Mardiyah, Mardiyah (Jurnal Manajemen Pendidikan, 2025)
Education plays a crucial role not only in achieving academic goals but also in preparing students to plan and develop their future careers. The difficulties faced by many graduates in securing jobs aligned with their interests highlight the importance of integrating career planning and development programs into higher education. This study aims to examine the concepts, implementation, challenges, and solutions of career planning and development in order to enhance students’ readiness for the workforce. Using a qualitative descriptive method with a literature review approach, data were collected from various national and international journals. The findings show that career planning functions as a process of self-identification and strategy formulation, while career development emphasizes improving skills, abilities, and adaptability to workplace dynamics. Implementation can be achieved through internships, education, workshops, and the use of digital technology. The novelty of this study lies in integrating career planning and development with an emphasis on digital technology and contextual challenges in Indonesia. Recommendations highlight the importance of leadership support, technological optimization, and aligning career paths with student goals to strengthen graduate employability.